Analisis Hubungan Antara Strategi Pemasaran dan Kepuasan Pelanggan di Platform E-Commerce - Melisa Melisa; Amelia Putri Ananda; Ratna Sari Hasibuan; Siti Suaibah Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the relationship between marketing strategies and customer satisfaction on e-commerce platforms in Indonesia. Effective marketing strategies are essential in facing intense competition in the digital world, especially in enhancing customer satisfaction, which influences loyalty and business sustainability. This research uses a quantitative survey approach involving 100 active users of Shopee and Tokopedia platforms. Data were collected through questionnaires and analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The results indicate a positive and significant relationship between marketing strategies and customer satisfaction, with a correlation value of 0.673 and a contribution of 45.3%. Digital promotions, personalized services, and loyalty programs are key factors in improving customer satisfaction. However, customer service aspects require more attention to support overall satisfaction. This study implies that e-commerce platforms must continuously develop integrated marketing strategies alongside quality service improvements to maintain and enhance customer satisfaction.